KOMBINASI EDUKASI NYERI DAN MEDITASI DZIKIR MENINGKATKAN ADAPTASI NYERI PASIEN PASCA OPERASI FRAKTUR - Nasriati R; Suryani L; Moh Afandi (IJNP (Indonesian Journal of Nursing Practices), 2016)
Post operation pain is a problem that can impede the patient recovery if not managed properly. Post operated patient should be able to adapt to  pain  perceived that they feels. Pain education and dzikir meditation were type of non-pharmalogical management to help patients controlling their pain. The aims of this study was to described the eﬀect of combination pain education and dzikir meditation to the adaptation of post operative pain in patient with fracture. This study used quasy experiment with pre-and post-test control group design. The sample in this study was 48 people’s were divided into intervention group and control group with 24 people’s in each group recruited by consecutive sampling. Statistical analysis used parametric test (Paired T test and T test independent) and non parametric (Wilcoxon signed Rank test dan Mann Whitney test). The results showed there were decrease pain intensity from 7 to 4,1 score and blood pressure from 124/80,4 mmHg to 120/75 mmHg in intervention. group with p0,05. Based on statistical test with p0.05 this showed that there were diﬀerences changes in pain intensity between the intervention group and control group signiﬁcantly. The conclusion of the research there was combination of pain education and dzikir meditation can reduce pain intensity but it doesn’t give any eﬀect to the blood pressure, pulse, and respiration in post fracture operated patient. Keyword : pain intensity, blood pressure, heart rate and respiration rate